Poverty and entrepreneurship in developed economies - Morris, Michael H.; Santos, Susana C.; Neumeyer, Xaver; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
This is the first in-depth examination of entrepreneurship and the poor within advanced economies. Entrepreneurship is presented as a source of empowerment that represents an alternative pathway out of poverty. The book explores the underlying nature of poverty and draws implications for new venture creation. This book fosters a richer dialog among academics, government officials, policy-makers, economic development professionals, bankers and the financial community, leaders of non-profit organizations, and others committed to moving beyond status quo solutions - committed to finding ways to help people create their own entrepreneurial pathways out of poverty.
Contents: 1. Understanding poverty -- 2. The nature of entrepreneurship -- 3. Entrepreneurship and the poor -- 4. Types of entrepreneurs and types of ventures -- 5. Opportunity horizons and the poor -- 6. The challenges of literacy among the poor -- 7. Technology and the poor -- 8. Building supportive infrastructure for low income entrepreneurs -- 9. Financing the ventures of the poor -- 10. Overcoming resource constraints -- 11. From vulnerability to sustainability: the challenges of planning and strategy -- 12. Making sense of the economics -- 13. Policies and programs to support low income entrepreneurship -- Index.
Includes index.
Description based on print record.
Keywords: Entrepreneurship; Poor; Electronic books